Role of youth centers in developing social responsibility - RAKAN, A.; AYMAN, A. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The study aims to identify the role of youth centers in developing individual responsibility towards society. The study used the social survey method. A random sample of 272 individuals was collected. The study concluded that there is a large role for youth centers in developing social responsibility towards society. According to these results, the study recommended not to restricting affiliation to youth centers with a specific age group, encouraging young people to affiliate with youth centers, and undertaking external visits to gain experience in this field.